2019
DOI: 10.1097/ipc.0000000000000713
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Rectovaginal Colonization and Antibiotic Susceptibility Pattern of Streptococcus agalactiae in Pregnant Women in Al-Zahra Hospital, Rasht, Iran

Abstract: Background Maternal rectovaginal colonization with group B streptococcus (GBS) is a main risk factor for vertical transmission of GBS to newborns and life-threatening neonatal invasive diseases. The aim of this study was investigation of the prevalence of anorectal and vaginal colonization with GBS in late of pregnancy by culture-based and polymerase chain reaction (PCR) methods and antimicrobial susceptibility patterns of the GBS isolates in Rasht, Iran. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Different β-lactam resistance percentage in commensal GBS has been reported from Iran. In one study, high-level resistance to penicillin (88.6%) was reported ( 26 ), while in other studies no resistant isolates were detected ( 21 , 27 ). It is noteworthy that in most of the studies minimum inhibitory concentration (MIC) of β-lactam agents was not investigated, and in the only one study from Iran, 27% of GBS isolates were resistant to penicillin at MIC of 1.5 μg/ml ( 28 ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Different β-lactam resistance percentage in commensal GBS has been reported from Iran. In one study, high-level resistance to penicillin (88.6%) was reported ( 26 ), while in other studies no resistant isolates were detected ( 21 , 27 ). It is noteworthy that in most of the studies minimum inhibitory concentration (MIC) of β-lactam agents was not investigated, and in the only one study from Iran, 27% of GBS isolates were resistant to penicillin at MIC of 1.5 μg/ml ( 28 ).…”
Section: Discussionmentioning
confidence: 94%
“…However, our findings showed that 44.4% and 29.6% isolates were resistant to erythromycin and clindamycin; respectively, and among these, one isolate (3.7%) had an iMLSB phenotype. In Iran, the erythromycin resistance rate in invasive and commensal GBS isolates was reported from 19.5 to 100%, and clindamycin resistance rate from 16.6 to 100% ( 21 , 26 – 33 ). Unfortunately, the mechanism of resistance to MLSB was less investigated in our region.…”
Section: Discussionmentioning
confidence: 99%